ASUHAN KEBIDANAN BERKELANJUTAN NY. “I” DI PUSKESMAS ANTANG PERUMNAS MAKASSAR - Nirwana; Endang Sulistyowati; Jumriana Ibriani; Aprilia Balsala (Jurnal Ilmiah Citra Kebidanan, 2025)
Pregnancy and childbirth are natural physiological processes that require quality nursing through the continuity of care approach to optimize maternal and infant health and to prevent complications. Continuity of care (coc) is a comprehensive approach in which a midwife provides continuous and continuous nursing care to women from pregnancy, childbirth, nifas, to family planning. This study describes the application of comprehensive obstetrics to Mrs. Adams. I, age 22, g1p0a0, ranging from trimester pregnancy iii to nifas and newborn care. Prenatal care includes the monitoring of the mother and fetus condition, including pain management with physical activities such as gym ball. The process of labor operated physiologically with non-pharmacological chaperones (endorphine massage) to relieve pain. Childbirth during which i-iv walked normally. During the nifas period, vital signs are monitored, the uterus uterus uterus uterus uterus, and the education of self-care. The baby is born spontaneously weighing 2900 grams, pb 46 centimeters, and apgar 8/10, then monitored through neonatal visits to ensure exclusive adaptation and breast-feeding. It emphasizes early detection of complications, lowered risk of maternal death, and postnatal family support. The upbringing involves a longitudinal case study design with a qualitative approach.